231k views
1 vote
Solve the equation, 4 - (x + 1) = 6.

x = -3
x = 3
x = -9
x = 9

2 Answers

2 votes

Answer:

Explanation:

The negative in front of the parenthesis changes the signs of the numbers and variables inside the parenthesis. We can rewrite as

4 - x - 1 = 6 and

3 - x = 6 so

- x = 3 and

x = -3

User Jay Adams
by
5.6k points
2 votes

Answer:

The answer to your question is x = -3

Explanation:

Equation 4 - (x + 1) = 6

- Subtract 4 in both sides

4 - (x + 1) - 4 = 6 - 4

- Simplify

- (x + 1) = 2

- Remove parentheses

- x - 1 = 2

-Add 1 to both sides

-x - 1 + 1 = 2 + 1

- Simplify

- x = 3

-Divide both sides by - 1

- x / -1 = 3 / - 1

- Simplify

x = -3